L’assurance au Canada au cours du dernier demi-siècle - Parizeau, Gérard (Assurances, 1982)
Over the past fifty years, the insurance industry in Canada has undergone rather significant modifications. While often reluctant to change, circumstances have compelled the insurance industry to adapt to the times by seeking out new solutions to old problems. In his article, our director, Mr. Gérard Parizeau, examines the principal aspects of these solutions from both the individual and collective points of view. Mr. Parizeau points out, in particular, the detrimental effects of inflation upon the real value of capital as well as the measures taken in an effort to counter or at least partially alleviate the effects thereof.